Orbitofrontal cortex and aggressive behavior in children ages 11 to 13 - Valencia-Ortiz, Andrómeda Ivette; Consuelos-Barrios, Mauricio; García-Cruz, Rubén; García-López, Eric (Journal of Basic and Applied Psychology Research, 2020)
One of the main points for successful child development is to achieve maturation of the Nervous System. However, growth can be affected by external factors linked to the family or school environment, which can cause behavioral, physical and socio-emotional disturbances to the development of the child, where social skills play a crucial role in preventing aggressive or violent behavior. The objective of this study was to determine the association between the orbitofrontal cortex and aggressive behavior in children from 11 to 13 years old, located in the city of Pachuca, Hidalgo. With a non-experimental design and a correlational scope, an intentional non-probability. A sample of 118 children participated. The participants were evaluated in two sessions, in the first with the Scale of Assertive Behavior for Children (CABS) and the second the Neuropsychological Battery of Executive Functions and Frontal Lobes (BANFE-2). A low and negative statistically significant correlation was found between aggressiveness and severe alteration in the orbitomedial cortex (r = -.273; p = <. 01). They were also highlighting the relationship between aggressiveness and severe alteration in the orbitomedial zone in males (r = -.302; p = <. 05).In conclusion, children who have a severe dysfunction in the orbitomedial cortex usually are more aggressive than those with an average or high score in this zone.